2016
DOI: 10.1039/c6ra10170d
|View full text |Cite
|
Sign up to set email alerts
|

Metallic 1T phase MoS2 nanosheets as a highly efficient co-catalyst for the photocatalytic hydrogen evolution of CdS nanorods

Abstract: A 1T–MoS2/CdS NRs photocatalyst shows enhanced photocatalytic activity because of the ohmic contact with low resistance between 1T–MoS2 and CdS NRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…For MoS 2 photocatalyst, researchers including Ho et al observed the correlation between HER activity and exposure level of MoS 2 edge site, which helped to embody the effect of MoS 2 structural characteristics on HER performance [76]. The charge transfer characteristics and the internal resistance of the TM(D)C material combined with Si have been studied by many researchers [77][78][79] revealing the relationship between the surface modulation and kinetic enhancement. In the case of Si photoelectrode modified by MoS 2, the performance and catalytic properties tend to be affected by its thickness [79,80].…”
Section: Electrochemical Impedance Spectroscopy (Eis) For Photoelectrmentioning
confidence: 99%
See 1 more Smart Citation
“…For MoS 2 photocatalyst, researchers including Ho et al observed the correlation between HER activity and exposure level of MoS 2 edge site, which helped to embody the effect of MoS 2 structural characteristics on HER performance [76]. The charge transfer characteristics and the internal resistance of the TM(D)C material combined with Si have been studied by many researchers [77][78][79] revealing the relationship between the surface modulation and kinetic enhancement. In the case of Si photoelectrode modified by MoS 2, the performance and catalytic properties tend to be affected by its thickness [79,80].…”
Section: Electrochemical Impedance Spectroscopy (Eis) For Photoelectrmentioning
confidence: 99%
“…The charge transfer characteristics and the internal resistance of the TM(D)C material combined with Si have been studied by many researchers [77][78][79] revealing the relationship between the surface modulation and kinetic enhancement. In the case of Si photoelectrode modified by MoS 2, the performance and catalytic properties tend to be affected by its thickness [79,80]. the correlation between HER activity and exposure level of MoS2 edge site, which helped to embody the effect of MoS2 structural characteristics on HER performance [76].…”
Section: Electrochemical Impedance Spectroscopy (Eis) For Photoelectrmentioning
confidence: 99%
“…Working with phase engineering involves taking advantage of innate properties for the desired processes. Du and co‐workers have pointed out that photocatalytic hydrogen evolution under visible‐light irradiation could increase by a factor of 35 with an optimized 1T‐MoS 2 /CdS NR hybrid system compared with the pure CdS NR system. Such an improvement was attributed to the variation of the 1T‐MoS 2 nanosheets.…”
Section: Spe For Redox Processesmentioning
confidence: 99%
“…Du et al have synthesized 1T‐MoS 2 /CdS NRs and 2H‐MoS 2 /CdS NR hybrids with various phases of MoS 2 nanosheets using hydrothermal methods. With a 10 wt% 1T‐MoS 2 /CdS nanorod heterojunction, the hydrogen generation rate was 794.93 µmol g −1 h −1 , which was ≈35‐fold and 4.5‐fold higher than that of pristine CdS nanorods (22.51 µmol g −1 h −1 ) and 2H‐MoS 2 /CdS nanorods (175.82 µmol g −1 h −1 ), respectively.…”
Section: Spe For Energy Conversion and Environmental Treatmentmentioning
confidence: 99%
“…[5][6][7] However, the rapid recombination of the photogenerated charge carriers and photocorrosion under light irradiation limits its wide application in photocatalysis. 8,9 ZnS is known as a wide band-gap semiconductor and is stable and resistant to photocorrosion. 10,11 It has been reported that the coupling of ZnS with CdS greatly enhances the photocatalytic activity for hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%